Water absorption behaviour of epoxy/acrylated epoxidized palm oil (AEPO) reinforced hybrid kenaf/glass fiber montmorillonite (HMT) composites - Rohani, Mustapha; Siti Noor Hidayah, Mustapha; M. J., Suriani; C. M., Ruzaidi; M., Awang (Institute of Physics, 2021)
The use of fiber-reinforced vegetable oil - polymer composites has increased in various technical fields. However, the long-term operating performance of these materials is still not well understood, limiting the development of these composites. In this study, the water absorption performance of hybrid composites, which consist of kenaf fiber and glass fiber as reinforcement, epoxy resin and acrylated epoxidized palm oil (AEPO) as a matrix, and montmorillonite (MMT) nano clays as a filler was evaluated with the function of different fibers layering order. The hand lay-up method is used to produce the composites with the variable number of kenaf fibers and glass fibers layer sequences. The water absorption kinetics of epoxy/AEPO reinforced hybrid kenaf/glass fiber-filled MMT composites are described in this paper. It has been observed that the water absorption rate of the composites depends on the fiber layering sequences. The alternative sequence of Glass-Kenaf-Kenaf-Glass and Kenaf-Glass-Kenaf-Glass composites layers exhibited the lowest moisture absorption rates of 7.61% and 7.63%, respectively.